Phytochemical investigations of Goniothalamus tapis and G. tapisoides, and kinetic mechanism studies of goniothalamin / Rosalind Kim Pei Theng - Rosalind Kim , Pei Theng (2020)
Phytochemical studies on two species of Annonaceae; Goniothalamus tapis and Goniothalamus tapisoides have been carried out. Isolation and purification of the crude extract of stem bark of G. tapis and G. tapisoides yielded seventeen compounds. G. tapis gave nine compounds; goniothalamin 1, isoaltholactone 41, 3-acetylisoaltholactone 151, cheliensisin A 22, garvensintriol 4, goniopyyprone 26, 7-epi-goniofufurone 49, stigmasterol 133 and β-sitosterol 134. Out of nine compounds, 3-acetyl-isoaltholactone 151 was identified as a new styryl-lactone. The skeleton is similar as the major compound, isoaltholactone 41. But 3-acetylisoaltholactone 151 have different functional group compared to hydroxyl group in isoaltholactone 41, which is acetyl group. As for G. tapisoides, eight compounds were acquired; goniodiol 3, 7-epi-goniodiol 10, 8-epi-9-deoxygoniopypyrone 24, goniomicin A 147, goniomicin E 152, goniomicin F 153, goniomicin G 154 and goniomicin H 155. Compounds 152, 153, 154 and 155 were identified as new styryl-lactones. The structure of all compound was elucidated using various spectroscopic methods; 1D-NMR (1H, 13C, DEPT), 2D-NMR (COSY, HSQC, HMBC, NOESY), UV, IR and mass spectrometry. Goniothalamin 1 is a major compound isolated from dichloromethane extract of G. tapisoides. A spectrophotometric kinetic study of hydrolysis of 1 has been carried out in alkaline and acidic medium at various temperature to determine the reaction mechanism of the hydroxide ion-catalyzed reaction. Alkaline hydrolysis undergoes monotonic reaction and pseudo-first-order rate constant (kobs). It showed linear relationship with the increase of concentration of NaOH, giving goniomicin A 147 as a product. Hydrolysis of 1 in alkaline medium involved the ring opening of the lactone moiety. As to acidic medium, hydroxonium ions will catalysed the cleavage of lactone ring and the intermediate product further undergoes dehydration to form a product with three consecutive double bonds. The products of both alkaline and acidic hydrolysis were characterized by 1D-NMR, 2D-NMR and mass spectrometry.